(3ebGeGJ GdMQjQjs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG YdeJ ef GdHjGf GdebGeI GdChdi JYQa HGdUfYGfjI MOK GdMGQK WhMJ Hi WhGFM GdRef Edi UfYGA Gdjef aONdJgG NGdj GdhaGV s
(3BNQgG (B:s
(3BNQ GdebGeGJ GdJi CfTCJgG HGdEYJRGR Efg Cgd GdJbhi hCgd GdeZaQI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1787s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdCOHs